2014
DOI: 10.1186/bf03352534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seismic ground motion and geological setting on the coseismic groundwater level changes caused by the 1999 Chi-Chi earthquake, Taiwan

Abstract: The groundwater level changes induced by the 1999 Chi-Chi earthquake were well recorded at the monitoring wells in and around the Choshui River alluvial fan, Taiwan, which is adjacent to the focal region. We analyzed the coseismic groundwater level changes related to the geological setting and seismic ground motion. In a typical fan area, the groundwater levels coseismically rose and those amplitudes increased as the ground acceleration and hydraulic conductivity became larger. In the slope area near the earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The water-level rise in unconfined aquifers in the plain and coastal area just after the main shock may be caused by in situ liquefaction or consolidation of sediments (Lai et al, 2004;Wakamatsu et al, 2017). Based on previous well-constrained regional groundwater flow models (Hosono et al, 2013;Kagabu et al, 2017;Ono et al, 2013), the area with water-level decreases is a groundwater discharge zone with significant upward flux.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…The water-level rise in unconfined aquifers in the plain and coastal area just after the main shock may be caused by in situ liquefaction or consolidation of sediments (Lai et al, 2004;Wakamatsu et al, 2017). Based on previous well-constrained regional groundwater flow models (Hosono et al, 2013;Kagabu et al, 2017;Ono et al, 2013), the area with water-level decreases is a groundwater discharge zone with significant upward flux.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…This result is similar to that of some other researchers. Koizumi et al (2004) suggested that using focal mechanism to explain coseismic changes has big discrepancy with the fact. Wang et al (2005) suggested that the causation of coseismic variation is the movement of ground surface and its aftereffect caused by seismic waves.…”
Section: Discussionmentioning
confidence: 95%
“…Seismologically oriented studies place emphases on the effects of pore pressure on deformation related to rock strength, post‐seismic deformation, and aftershocks [e.g., Nur and Booker , 1972; Jónsson et al , 2003]. Hydrologically oriented studies, on the other hand, focus on the behavior of seismically induced hydrologic changes manifested by groundwater level fluctuation [e.g., Roeloffs et al , 1989; Lai et al , 2004; Akita and Matsmoto , 2004]. Pore pressure changes have been used as a sensitive strain meter in seismic experiments [ Roeloffs , 1996].…”
Section: Introductionmentioning
confidence: 99%